The problem of choice: original drug or generic? Emphasis on rosuvastatin - O. A. Polyakova; O. D. Ostroumova (Столичная издательская компания, 2022)
An increase in the life expectancy of the population and the number of polymorbid patients with a combination of two or more diseases in different age categories, including among young people, has led to a significant increase in the cost of medical care in the field of public health. The transition from original drugs to generic ones has become a common measure to contain these costs. While this is an important goal for healthcare systems around the world, the impact of this practice on patient outcomes needs to be carefully considered. In some cases, generics may represent a suitable alternative to branded products, but this is not always the case. In particular, studies have shown that changing the drug can negatively affect not only patients' adherence to treatment, but also clinical outcomes, and a subsequent increase in the total cost of treatment, therefore, the use of generics in clinical practice still causes caution and concerns on the part of both the doctor and the patient. Due to the high prevalence of dyslipidemia and hypercholesterolemia both worldwide and in Russia, in this review the problem of choosing an original drug or generic is described by the example of such a hypolipidemic agent as rosuvastatin. According to numerous studies, rosuvastatin is one of the most potent and widely prescribed statins. Considering that most of the clinically significant effects of this drug are demonstrated in relation to its original form, the review emphasizes the importance of prescribing the original drug rosuvastatin in routine clinical practice.